Knowledge and Behavior as Risk Factors for Intestinal Worm Contamination on Raw Vegetables Food Traders in Pakusari District Jember Regency - Yoga Setyo; Wiwien Sugih Utami; Heni Fatmawati; Yunita Armiyanti; Bagus Hermansyah (Jurnal Ilmiah Kesehatan, 2023)
Intestinal parasites are one of the leading public health problems worldwide, with an incidence of 24% worldwide and 45-65% in Indonesia. Intestinal parasites, especially intestinal worms, or soil-transmitted helminths (STH), significantly contribute to gastrointestinal diseases worldwide. Intestinal worm infections occur in rural and urban populations, especially in people who have the habit of eating with dirty hands, using unhygienic toilets, and consuming contaminated food, water, or soil. Fresh vegetables are a means that support parasitic intestinal infections, especially for traders who must be able to prevent intestinal worm contamination in fresh vegetables. Consumption of raw vegetables can be a source of intestinal worm infection, thereby increasing the prevalence of foodborne diseases. This type of research is analytic observational with a cross-sectional study design. Samples in the form of fresh vegetables were taken from fresh vegetable traders in Pakusari District, Jember Regency and then processed by the sedimentation method and then observed using a microscope to identify intestinal protozoa. Food safety knowledge was assessed using a questionnaire, and the behavior of food traders was assessed by researchers using observation sheets. The bivariate analysis showed that proper handwashing behavior was related to intestinal worms in fresh vegetables (p<0,05). Other knowledge and behavior variables were unrelated to intestinal worms' presence. The intestinal worm species found is a type of Hookworm.